Religion and the Problem of Modernization (on the example of M.Weber and S.Bulgakov) - Иван Владимирович Забаев (Journal of Economic Sociology, 2010)
The author discusses Weber’s interpretation of the research approach to the process of how the religion influenced the new type of economy and the new socio-cultural system. This approach is compared to the way of how this idea was considered in Russia in the same period of time. The classic papers written by Bulgakov were taken into consideration for this purpose. While we compare these approaches we take Marx’s publications as “intellectual mediator” as both Bulgakov and Weber debated with him. The paper focuses on the proposed ways of analysis of the impact of religion on the modernization, which is mostly considered in the context of rationalization.